Identifikasi Batuan PAF, NAF dan UNCERTAIN dengan Menggunakan Metode NTAPP Pada Area PT. Trubaindo Coal Mining, Melak-Kalimantan Timur - Irviansyah, Alfian; Sitorus, Saibun; Panggabean, Aman Sentosa (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2020)
The research about identification of PAF, NAF and uncertain rock using NTAPP method in the PT. Trubaindo Coal Mining has been done. This research was conducted as an effort to control the potential for the formation of acid mine drainage, with identifying the types of mine rocks using certain testing methods. Some important parameters such as Total Sulfur Level, Slurry pH, Total Actual Acidity (TAA), Chromium Reducible Sulfur (CRS) and Acid Neutralizing Capacity (ANC) using the NTAPP method on mine rocks have been determined to identify mining rock category categories. Based on the results of tests on 101 samples, 63 samples were identified included in the category of rocks that are not NAF (Slurry pH value = 4.1 - 8.9; Total Sulfur = 0.01-0.60 %; CRS = 0.01-0.10 % and NTAPP = 0.030-0.959 %), 38 samples were classified as PAF (pH Slurry = 2.9-7.9; Total Sulfur = 0.01-5.10 %; CRS = 0.11-2.04 % and NTAPP = 0.053-4.571 %), and no sample was included in the uncertainty category.